2009
DOI: 10.1007/s10584-009-9764-2
|View full text |Cite
|
Sign up to set email alerts
|

How well do integrated assessment models simulate climate change?

Abstract: Integrated assessment models (IAMs) are regularly used to evaluate different policies of future emissions reductions. Since the global costs associated with these policies are immense, it is vital that the uncertainties in IAMs are quantified and understood. We first demonstrate the significant spread in the climate system and carbon cycle components of several contemporary IAMs. We then examine these Climatic Change (2011) 104:255-285 components in more detail to understand the causes of differences, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 48 publications
4
102
0
1
Order By: Relevance
“…For comparison the dashed line denotes the path for the median case of f = 0.6 which represents an equilibrium climate sensitivity of around 3 C. We begin by considering the difference between the temperature response functions along this path representing a single model run (dashed line). This portion of the experiment, that is with an implied equilibrium climate sensitivity around 3 C, is very similar to the one carried out by van Vuuren et al (2011) and despite differences in the model vintages we find very similar results. 7 Initially, that is over the first 10-20 6 If model specific uncertain parameters are allowed to vary the primary results due not differ, and any differences in the plots presented are negligible.…”
Section: Temperature Dynamics For a Sustained Forcingsupporting
confidence: 80%
See 1 more Smart Citation
“…For comparison the dashed line denotes the path for the median case of f = 0.6 which represents an equilibrium climate sensitivity of around 3 C. We begin by considering the difference between the temperature response functions along this path representing a single model run (dashed line). This portion of the experiment, that is with an implied equilibrium climate sensitivity around 3 C, is very similar to the one carried out by van Vuuren et al (2011) and despite differences in the model vintages we find very similar results. 7 Initially, that is over the first 10-20 6 If model specific uncertain parameters are allowed to vary the primary results due not differ, and any differences in the plots presented are negligible.…”
Section: Temperature Dynamics For a Sustained Forcingsupporting
confidence: 80%
“…The important work of van Vuuren et al (2011) and Warren et al (2010) are the exception and provide a careful examination of the climate modules within this class of IAMs through inter-model comparisons with more complex models, including three-dimensional Atmosphere-Ocean General Circulation Models (AOGCMs). These studies provided a comprehensive look into the climate models contained within IAMs, examining in detail the links between emissions and atmospheric concentrations, concentrations and radiative forcing, and radiative forcing and temperature among other aspects of the models.…”
Section: Introductionmentioning
confidence: 99%
“…van Vuuren et al (2011), Marten (2011 and others have evaluated the predictive performance of the simple climate modules in IAMs. In order to study the economic consequences of uncertainty about extreme warming in IAMs, it is helpful to first get a conceptual handle on the underlying physical uncertainties that drive the economic analysis.…”
Section: The Science Of Extreme Warmingmentioning
confidence: 99%
“…Van Vuuren et al (2011b) presented a detailed comparison of the representation of the carbon cycle and climate system in different IAMs. It was concluded that the representations of the carbon cycle in IAMs mostly lie within the range of earth system models (referred to as Bexpert models^).…”
Section: Introductionmentioning
confidence: 99%